Lenny Krayzelberg's turn at 50 m of his gold medal 200 m race at the 1999 Pan Pacific Championships in Sydney
Video analysis of Lenny Krayzelberg's turn at 50 m of his gold medal 200 m race at the 1999 Pan Pacific Championships in Sydney, 43 frames. Lenny Krayzelberg's turn features several aspects of good movement mechanics. - There are no inertial lags in the total sequence. One part of the sequence flows into the next. - Rotation to change direction, once it is initiated, is completed quickly. - The double-leg kick is a distinct action and bears no resemblance to a butterfly stroke's "dolphin" action. The reason for that is the kick in butterfly is a reaction to arm movements and is required to keep the swimmer streamlined (when done well). It does add some horizontal propulsion but not to the same extent as that developed in the double-leg kick. In butterfly, the kick develops both vertical and horizontal forces. In the double-leg kick, all forces result in horizontal propulsion. - Finally, the streamlining of the swimmer is excellent. The stable leading edge (hands, arms, head, and torso) presents a desirable minimized cross-sectional area to the oncoming fluid and does not waste energy by causing water to move unnecessarily. This sequence is a fine demonstration of how to perform a modern backstroke turn into, on, and away from the wall.